Strategi Badan Usaha Milik Desa Tentang Pengelolaan Sampah Di Desa Simpang Sungai Duren Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - rusli; rusli, rusli (DEMOS: Journal of Demography, Ethnography and Social Transformation, 2022)
The purpose of this study was to determine the distribution of illegal landfills in the Simpang Sungai Duren village, Jambi sub- district, outside the city of Muaro Jambi Regency. This study uses an empirical approach. Based on direct observations in the field, it was found 3 locations of illegal waste disposal sites (TPS) in the village of Sungai Duren intersection. first on ness road RT 1, second in front of the UIN STS JAMBI campus, and the third location in RT 02. Village government constraints: lack of public awareness in disposing of waste in its place, facilities and infrastructure for the BUMDes program, lack of adequate Human Resources (HR) running the BUMDes program, the absence of clear regulations or policies from the village government regarding waste management, and the unavailability of temporary waste disposal sites in the Simpang Sungai Duren village. The village government's strategy in overcoming waste problems such as making PERDES on waste problems and making RAPERDES about profit sharing between DESA and BUMDes, the Village Government is trying to submit an application proposal to the Environment regarding waste management tools, both chopping machines or sorting machines to be used as fertilizer.